Metagenomic analysis of the salivary microbiota in patients with caries, periodontitis and comorbid diseases - Cong Shi; Liting Cai; Zhe Xun; Saiwei Zheng; Fangyang Shao; Bingjie Wang; Ruixin Zhu; Yuan He (Elsevier, 2021)
Background/purpose: Previous studies have suggested that there is a mutual antagonism between caries and periodontitis. This research aimed to investigate the ecological connection and bacterial interaction of these two diseases. Materials and methods: We profiled and analyzed the salivary microbiota from 124 individuals (including 38 caries patients, 34 periodontitis patients, 15 comorbid diseases patients, and 37 healthy controls) by using 16 S rRNA gene sequencing and bioinformatics approaches, and also quantified their salivary bacteria loads via quantitative real-time PCR. The putative biological functions of the salivary microbiome of the different groups were predicted by PICRUSt. Results: We observed that both the total bacteria loads and the overall microbial richness in the saliva of the periodontitis group were higher than that in the healthy group. The principal coordinate analysis (PCoA) showed that the caries, periodontitis and healthy groups were separated from each other, and that the samples from comorbid diseases were located at the overlap of caries and periodontitis groups. Using LEfSe analysis, 20 differentially abundant genera were identified as potential biomarkers. These genera also performed complicated interactions among the four groups. Additionally, the PICRUSt analysis indicated caries-related and periodontitis-related functions (e.g., carbohydrate metabolism and bacteria proliferation) respectively. Conclusion: We disclosed the significant differences in the salivary bacterial community under caries, periodontitis and comorbid diseases. The periodontitis group was marked by the increased complexity of the salivary microbiota. The result may have vital clinical significance to the screening and early treatment of caries-active and periodontitis-active individuals.